Krieg und Frieden in Europa: eine Rolle für ,,Brinkmanship“? - Klaus Beckmann (Wirtschaftsdienst, 2025)
– This article analyses aspects of the conflict between Russia and Ukraine in its international context from a game theory perspective, with particular attention to the possible use of the brinkmanship strategy by US President Donald Trump.
Keywords: C72; N40; 330; Krieg; Friedenssicherung; Internationale Sicherheit; Europa; Krieg; Friedenssicherung; Internationale Sicherheit; Europa